Pilgrims - Gilbert, Elizabeth, 1969- (New York : Penguin Books, 2007)
A collection of twelve short stories by contemporary American author Elizabeth Gilbert.
Kirkus Starred.
Library Journal.
Publisher's Weekly.
Adult
Keywords: Short stories; United States -- Social life and customs -- 20th century -- Fiction; United States -- Social life and customs -- Fiction